Association of plasma vitamin C concentration to total and cause-specific mortality: a 16-year prospective study in China. Issue 12 (12th August 2018) - Wang, Shao-Ming; Fan, Jin-Hu; Taylor, Philip R; Lam, Tram Kim; Dawsey, Sanford M; Qiao, You-Lin; Abnet, Christian C
Abstract : Background: Vitamin C insufficiency occurs across many countries and has been hypothesised to increase risk of various diseases. Few prospective studies with measured circulating vitamin C have related deficiency to disease mortality, particularly in low-income and middle-income countries. Methods: We randomly selected 948 subjects (473 males and 475 females) aged 53–84 years from a Chinese cohort and measured meta-phosphoric acid-preserved vitamin C concentrations in plasma samples collected in 1999–2000. A total of 551 deaths were accrued from sample collection through 2016, including 141 from cancer, 170 from stroke and 174 from heart diseases. Vitamin C was analysed using season-specific quartiles, as a continuous variable and as a dichotomous variable based on sufficiency status (normal >28 µmol/L vs low ≤28 µmol/L). HRs and 95% CIs were estimated using Cox proportional hazards models. Results: We found significant inverse associations between higher plasma vitamin C concentrations and total mortality in quartile (HRQ4 vs Q1 0.75, 95% CI 0.59 to 0.95), continuous (HRq20umol/L 0.90, 95% CI 0.82 to 0.99) and dichotomous analyses (HRnormal-vs-low 0.77, 95% CI 0.63 to 0.95). We observed significant lower risks of heart disease (ptrend-by-quantile =0.03) and cancer deaths (pglobal-across-quantile =0.04) for higher vitamin C, whereas the association was attenuated for stroke in adjusted models. Similar inverse associations were found when comparing normal versus low vitamin C for heart disease (HRnormal-vs-low 0.62, 95% CI 0.42 to 0.89). Conclusion: In this long-term prospective Chinese cohort study, higher plasma vitamin C concentration was associated with lower total mortality, heart disease mortality and cancer mortality. Our results corroborate the importance of adequate vitamin C to human health.